Modified RSA Cryptosystem in a cloud based environment - Sahay, Harsh (International Journal of Computer Sciences and Engineering, 2019)
A traditional RSA Cryptosystem is based on only two prime numbers which is an efficient algorithm for preventing an unauthorized access over the internet. But there are some drawbacks of RSA cryptosystem, such as its high computational time. The primary motivation of our work is to reduce average computational time and provide better data security compared to traditional RSA. In this work we are modifying basic RSA cryptosystem algorithm by using three prime numbers which provides better data security as compared to standard RSA algorithm. Instead of applying RSA over each data unit, multiple data units are merged together to form one merged unit. The modified RSA is applied on the merged unit to form a cipher text which is sent by the sender. For merging multiple data units into single data unit, Cantor’s pairing algorithm has been used. At the receiver’s end the cipher text sent is received. The cipher text is deciphered using our modified RSA algorithm. Then this merged data unit is separated (unpaired) using Cantor’s unpairing algorithm. The highlight of this work is that, it increases the efficacy of the asynchronous cryptography (as compared to traditional RSA). The proposed framework increases security and reduces the average time taken for sending the data from sender to receiver. We are showing all procedures in a cloud environment.